Quantification of DDX3Y, RBMY1, DAZ and TSPY mRNAs in testes of patients with severe impairment of spermatogenesis - Lardone, M.C.; Parodi, D.A.; Valdevenito, R.; Ebensperger, M.; Piottante, A.; Madariaga, M.; Smith, R.; Pommer, R.; Zambrano, N.; Castro, A. (Molecular human reproduction, 2007)
Y chromosome microdeletion is the most important genetic cause of impairment of spermatogenesis. Nevertheless, a significant proportion of patients with spermatogenic failure do not have this condition. This study investigated the expression level of AZF genes, DDX3Y (DBY), RBMY1, DAZ and TSPY in testicular tissues of 42 subjects with impaired spermatogenesis compared with 33 with normal spermatogenesis. Histopathological evaluation was performed in all subjects and tissues were classified according to Johnsen Score. Transcript amounts were determined by quantitative-competitive RT–PCR. Patients with complete Sertoli cell-only syndrome (SCOS) did not exhibit RBMY1, DAZ and TSPY gene expression, however, we detected very low expression of DDX3Y transcript. Tissue samples with focal SCOS showed significantly decreased expression of all genes (P < 0.001). Maturation arrest and hypospermatogenesis tissues expressed significantly low levels of DDX3Y testicular transcript (P < 0.001), while the mRNA levels of the other genes were similar to that in tissues from the normal spermatogenesis group. Negative or diminished gene expression of DDX3Y, RBMY1, DAZ and TSPY in tissues samples with SCOS or focal SCOS reflects the absence or the lower number of germ cells, respectively. The finding that the testicular transcript of DDX3Y is significantly decreased in patients with severe spermatogenenic failure, especially in those presenting maturation arrest, suggests an important role of DDX3Y during spermatogenesis.